ENHANCING CUSTOMER-INDUSTRY RELATIONSHIP USING HYBRID MULTI CRITERIA DECISION MAKING METHOD - Deepak Kumaar Arul; Ashwin Srikanth; Shankaranarayanan V; Thenarasu M (International Journal for Quality Research, 2023)
This study explores the ways in which Customer Relationship Management (CRM) can be used to increase the effectiveness of the organizational interface toward customer satisfaction. The purpose of this study is to decrease the customer defection rate and increase overall customer satisfaction (customer-industry relationship), by developing software using a hybrid Multi Criteria Decision Making method (MCDM) for a company taken as a case study. In order to decrease the customer defection rate, the important criteria are ranked using the Fuzzy Analytical Hierarchy Process (FAHP) and their corresponding weights are found by constructing a pairwise comparison matrix and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). For improving product performance and service levels, a novel mathematical framework integrated with four different methods of normalization is also introduced. After implementing the software, the customer satisfaction rate substantially increased from 39% in January to 76% in February.